ICT USE IN UNIVERSITY OF ELBASAN AND ITS OBSTACLES - Luan Bekteshi (European Scientific Journal, ESJ, 2015)
Information and Communication Technology is a major transforming force in today’s global society. The development and use of computers and ICT may have been the only important factor that has greatly changed the organisations and society in the last decades by revolutionizing the way of life. ICT has become an integral part of the daily life. Education is an important sector that has been affected by the use of ICT, which is being massively used in the auditoriums of the Albanian universities to improve and enhance the teaching and learning process. The functionality of ICT is contributing in the application of innovations in activities in and out of university auditoriums, thus considerably increasing the interaction between lecturers and students. The challenge in the use of ICT in education is to define how to better use ICT in improving the quality of teaching and learning, in sharing knowledge and information, thus better meeting the needs of society, lowering the education costs, and improving and increasing the efficiency of the education system. This study has been conducted during October 2014 - March 2015 at the “Aleksander Xhuvani” University of Elbasan, and aims to present a view of the level of ICT use in this university as an administrative means and as an auxiliary tool in the process of teaching and learning, and the obstacles in making the use of ICT massive. The collected data are used to draw conclusions and give recommendations to make the necessary changes to have a better use of ICT in the Albanian universities, and make it more efficient in serving teaching and the education system.